If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3t + -2t + 5 = 10 Reorder the terms: 5 + 3t + -2t = 10 Combine like terms: 3t + -2t = 1t 5 + 1t = 10 Solving 5 + 1t = 10 Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + 1t = 10 + -5 Combine like terms: 5 + -5 = 0 0 + 1t = 10 + -5 1t = 10 + -5 Combine like terms: 10 + -5 = 5 1t = 5 Divide each side by '1'. t = 5 Simplifying t = 5
| -14+5x=-12 | | 8z-7=9z | | 2x+4x+12-5= | | 6=-3L | | 3x+6+7x+4= | | 3(p-2)=18 | | 4n-7-2=17 | | 2R=20-3R | | 80v^3+16v^2+60v+12=0 | | x-9=x+15 | | 5N=4N+1 | | 1/2(6x-8) | | 2x-11=2x-11 | | 2M+3=1 | | -3v-5=-10 | | -4c-3=1 | | 8x+2-3x-4= | | 5d+2c= | | x/8=1246 | | 13w-15w=4 | | -5E=35 | | 4x-5=2x-x | | 5(Y-10)=0 | | -9f-4+f=20+16f | | x/4-5=6 | | 20=x-20x | | (4x^3-12x)+(-2x^3+10x)= | | 2x(3-y)=14x | | 5x+10=7x-28 | | 6(-3-x)-2x=14 | | I+1=-2 | | 19-x+13=2(x+13) |